THE ROLE OF CARVEDILOL IN THE PREVENTION OF CARDIOMYOCYTE APOPTOSIS CAUSED BY ACUTE MYOCARDIAL INFARCTION - A. N. Zakirova; B. N. Garifullin; N. E. Zakirova (Столичная издательская компания, 2017)
Data on the mechanisms of cardiomyocyte apoptosis in myocardial infarction are presented. It has been experimentally established that the ratio of the number of cardiomyocytes with signs of apoptosis and necrosis is 30:1 already 2 hours after acute artery occlusion. This fact points out the leading role of apoptosis in cardiomyocyte death in acute period of myocardial infarction. Cardiomyocyte apoptosis makes a significant contribution in myocardial remodeling and left ventricular dysfunction after myocardial infarction. The essential role of active forms of oxygen in the development of cell apoptosis after reperfusion was proved in experimental data. Carvedilol is a third-generation beta-blocker with additional pleiotropic and antioxidant effects. The multifactorial positive influence of carvedilol on apoptosis prevention gives the opportunity to adopt experimental results into real-life clinical practice. It was established in vivo that administration of carvedilol just after start of coronary reperfusion decreases by 77% the number of cells suffered from apoptosis. Carvedilol has antioxidant effects and prevents cell apoptosis due to reduction in calcium concentration in mitochondrial matrix. The experimental results and the data of large randomized clinical trials give an opportunity of using carvedilol in treatment of myocardial infarction to decrease necrotic zone and prevent cardiomyocyte apoptosis.